Przestrzenne formy upamiętniania Zagłady - Posłuszny, Łukasz (Aureus, 2014)
This book is a synthesizing reflection on the Holocaust commemoration, in which space becomes a starting point for discussion. The author understands space primarily as an amalgam of physical and social components, where various commemorative processes may occur. The first part of the book draws attention to the material aspect of space, which determines its character and function. Material culture has been a long ignored and depreciated dimension of human culture in the humanities and social sciences, because it was perceived as passive and fully controlled by human will, and therefore insignificant in the course of social and historical processes. An example of the Nazi system perfectly illustrates how important were the restrictions and prohibitions on the usage of mundane objects, and in general, the whole material culture in relation to macro and micro space management — the state, cities, neighborhoods and houses, but also parks and swimming pools, factories and offices or shops and theaters. The importance of things and space was also clearly visible in exploitative policies present in overcrowded ghettos and concentration and death camps. For this very reason, when we study spatial forms of Holocaust commemoration, it should be acknowledged that the first traces, proofs and mementoes of the murdered were their things. The first "monuments" showing the enormity of the destruction are thus primarily gigantic piles of objects — shoes, glasses, toys, clothes, suitcases, toothbrushes, etc., which together with the extensive camps’ space try to recall the scale of a crime impossible to understand or imagine. The first chapter shows the importance of introducing the material dimension in thinking about space and commemoration, and it ends with a question about one of the key concepts for the book, a monument, which can be understood as both object (singular or plural) and architecture (sculptures, buildings, highways). However, the term monument tends to be used rather in a later and traditional sense, as an architectural, figurative form commemorating the heroic deeds, carved in stone or cast in bronze. Therefore, the next chapter reconstructs this narrower line of thinking, together with a discussion about what form a monument commemorating a subject as delicate and sensitive as the Holocaust should take on. This leads to an idea of the counter-monument, the concept which was supposed to be the answer to the mentioned representational dilemma on the one hand, and which would disassociate it from the Nazi’s traditional monuments on the other hand. This chapter clarifies the counter-monument definition and explains the misunderstandings and confusions generated on the basis of this concept by following the dynamics of the new commemorative form and by investigating monuments from the ‘80s and ‘90s erected in Germany. In the next chapter, I examine various forms of the Holocaust commemoration in Berlin, a city famous for its bold, monumental, and even controversial projects. We find among them the entire spectrum of memorials – big, monumental, and abstract forms, like Peter Eisenman’s Memorial to the Murdered Jews of Europe or Daniel Liebeskind’s Jewish Museum Berlin; flat, invisible, and employing the idea of emptiness, like Christian Boltanski’s Missing House or Micha Ullman’s Book Burning Memorial; the dispersed and decentralized, like Renata Stih and Frieder Schnock’s Memory Places or Gunter Demnig’s Stumbling Blocks. I enrich descriptions of the monuments by signaling at this point their second, extended life, which manifests itself in the alternative modes of (mis)use, consisting of various social activities or artistic performances. The formal wealth of the outlined projects creates a wide panorama of possible solutions to the Holocaust commemoration problems. However, the discussions accompanying the building of monuments and their "future life" after realization emphasize the importance of the social component that permeates the biography of the monument, and therefore significantly influences its foreseen design. The book also addresses the relationship of space, place and memory in a specific situation, when commemoration is performed secretly or remains as unrealized potential. Although place is the most common space associated with memory, today the nature of this relationship changes, and is what indicates popularity and employment of such terms as Marc Augé’s non-places or Pierre Nora’s site of memory. I include and develop these concepts about space and memory in my reflections to describe qualitatively different phenomena occurring in Central and Eastern European countries. These are unsettling places in rural areas like glades or parking lots, markets and playgrounds in urban settings. I link them to the post-war time and modernization processes and call them sites of non-memory and non-sites of memory. Another part of the book deals with a completely different form of commemoration called Mystery of memory. Grodzka Gate - NN Theatre in Lublin initiated it in 2000 and as a form it situates itself closer to the art of theater than architecture. Real spaces and places of everyday interactions become a stage for these performances, such as the “Jewish town” in Lublin or the Majdanek concentration camp. The minimalist scenography modifies space and reveals its previously unseen dimensions, while the actors — residents and people especially related to places like survivors and Righteous Among the Nations — are involved in the course of the show thanks to various rituals and symbolic gestures. The performance should be distinguished from social actions, because it incorporates tools known from religious rituals and art, which together saturate the mystery of memory with an aura of uniqueness. The last discussed commemoration mode takes the form of exposition space. I examine an exhibition concerning the fate of the incarcerated children presented in one of the barracks of the Majdanek State Museum in Lublin. The Primer – Children in Majdanek Camp is unique for several reasons. First, because even though it is exhibited in the camp barrack, it uses a completely different filter to tell the story of the camp in comparison to the exhibitions in the rest of the barracks. For this reason, one experiences immersing oneself in all subsequent levels of space and narrative accompanying them – at first, in a general narrative about the camp, and later in a specifically arranged space marked by children’s experiences, their language and thinking, and hence formed in a way more accessible for younger visitors. Second, the exhibition resigns from didacticism and distancing descriptions, and takes an advantage of eyewitnesses and survivors’ testimonies instead. Third, the exhibition space evokes an aura of strangeness similar to a fairy tale or a dream. It is accomplished thanks to the arrangement of various, usually highly symbolic material objects, and by favoring the fragrance and phonic sensations, movement, while belittling visual stimulations. The exhibition creates an impression of a place open to thinking and experiencing, and functions as an asylum, a radically different form to its camp surrounding characterized by a more overwhelming and austere space.
Spatial forms of Holocaust commemoration
Keywords: space and place; memory studies; commemoration and memory; Holocaust studies; monuments; sites of memory; counter-monuments